The other scene in El lenguaje de las sirenas by Mariana de Althaus - Gallegos Santiago, Óscar Giovanni (2022)
This article aims to demonstrate how the fantastic in conjunction with notions such as “cholo” and “taki onkoy” are strengthened to open new perspectives regarding the classic concepts of discourse, power and ideology. To this end, the play El lenguaje de las sirenas (2012) by the peruvian writer Mariana de Althaus is analyzed, in which a “chola siren”appears stranded on the shore of a peruvian beach. It is at that moment that the song of this mestizo siren (taki onkoy) will confront not only the practices and discourses of the characters, but also their Western worldview, their subordinate condition, and the frantic noise of capital prior to the true horror. For this reason, rather than analyzing what is said in the work, we are interested in capturing the rumor of the unsaid, the interstices of this ancient silence, the incomprehensibility of that “other scene”.